Adobe Photoshop CS/CS2 breakthroughs - Blatner, David (Peachpit, 2005)
Adobe Photoshop is industry standard digital image software and users are hungry for solutions to their myriad concerns--from how best to manage the program's sometimes unwieldy interface to how to use the new Vanishing Point tool. Photoshop guru David Blatner has scoured the online forums, interviewed Adobe engineers, and gathered together answers to over 200 of the most-commonly asked questions. Written in a sassy, fun-to-read style, this book tackles every major Photoshop problem with a lay-it-on-the-line solution. Adobe Photoshop CS/CS2 Breakthroughs is for anyone who has been using Photoshop long enough to realize that the solution to their problems isn't always as obvious as one would expect.